Effects of simulated multi-sensory stimulation integration on physiological and psychological restoration in virtual urban green space environment - Song, Chen; Cao, Saixin; Luo, Hao; Huang, Yinghui; Jiang, Siwei; Guo, Baimeng; Li, Nian; Li, Kai; Zhang, Ping; Zhu, Chunyan; Fu, Erkang; Jiang, Mingyan; et al. (Frontiers in Psychology, 2024)
Virtual urban green environment images and audio stimuli had been proven to have restorative effects on subjects' physical and mental health. In this area, researchers predominantly focused on visual, auditory and olfactory aspects, while tactile and gustatory senses have been minimally explored. However, the optimal combination of sensory stimuli for promoting physical and mental recovery remains unclear. Therefore, a simulated sensory stimulation approach involving 240 participants was employed, with 30 individuals included in each of the eight experimental groups: the visual-auditory (VA), visual-auditory-olfactory (VAO), visual-auditory-tactile (VAT), visualauditory-gustatory(VAG), visual-auditory-olfactory-tactile (VAOT), visual-auditory-olfactorygustatory (VAOG), visual-auditory-tactile-gustatory (VATG), and visual-auditory-olfactory-tactilegustatory (VAOTG) groups. This study aimed to explore the differences in participants' physiological and psychological health recovery after exposure to different combinations of simulated sensory stimuli in virtual UGSs. The results indicated that the following: (1) In terms of physiological recovery, the blood pressure of the 8 experimental groups decreased significantly after the experiment, indicating that the virtual urban green space environment has a certain recovery effect on physiological state. The combination of VAOTG stimuli in the multisensory group resulted in the best blood pressure recovery (p < 0.05). Tactile is an important sense to enhance the physiological recovery effect. Olfactory-tactile or tactile-gustatory stimuli interactions significantly enhance physiological recovery, emphasizing the importance of tactile stimulation in improving physiological recovery.(2) In terms of psychological recovery, the common trigger of olfactorygustatory is the most key element to enhance psychological recovery through multi-sensory stimulation of virtual urban green space environment. VAOG stimulation had the best effect on psychological recovery (p < 0.05), followed by VAOTG stimulation (p < 0.05). Gustatory is an important sense to enhance the psychological recovery effect, and both the tactile-gustatory interaction and the olfactory-gustatory interaction significantly enhance the recovery effect. At the same time, the psychological recovery effect obtained by four or more sensory combinations was higher than that obtained by two or three sensory stimulation groups. This study confirms more possibilities for ways to restore physical and mental health through virtual natural environments. It expands the research on the benefits of virtual nature experience and provides theoretical support for the application of this method.